Geochemical constraints on the provenance, mineral sorting and subaerial weathering of Lower Jurassic and Upper Cretaceous clastic rocks of the eastern Pontides, Yusufeli (Artvin), NE Turkey - Dokuz, Abdurrahman; Tanyolu, Erkan (Tubitak Scientific & Technological Research Council Turkey, 2006)
An integrated petrographic and geochemical study of the shales and sandstones of Early Jurassic and Late Cretaceous age in the Yusufeli area ( Turkey) was carried out to obtain more information on their provenance, sedimentological history and tectonic setting, as well as to evaluate the influence of weathering, hydraulic sorting and recycling processes upon source-rock signature. Depending on their matrix and mineralogical content, the Lower Jurassic sandstones are identified as arkosic arenite and wacke, while the Upper Cretaceous sandstones are defined as lithic arenite and wacke. Elemental ratios such as La/Sc, Cr/Ni, Co/Th, Th/Sc and Cr/Th indicate a mafic source for the majority of each of the sandstone sequences. However, in several samples, high Th/Sc and low Cr/Th ratios suggest a contribution from a felsic source. Using element-ratio diagrams, all of the samples plot along a curve consistent with a two-component mixing model, consisting of a dominant mafic and a subordinate felsic source. The relatively low Cr/Ni ratios provide no support for significant amounts of ultramafic lithologies in the source area. The lower trace-element contents of the studied sandstones in relation to post-Archean Australian shales (PAAS), which are representative of the composition of the upper continental crust, indicate that recycling processes in their source areas were probably less intense than those of the PAAS. The more LREE-depleted patterns of the shales relative to sandstones likely do not reflect changes in source-area composition but, rather, variations in mineral sorting, chemical weathering and/or sediment recycling. Chemical index of alteration ( CIA) indices observed in the Lower Jurassic and Upper Cretaceous sediments ( average of 53 & 46, respectively) suggest that their source area underwent moderate degrees of chemical weathering processes. However, an upward increase in the values of the CIA indices in the Lower Jurassic profiles may indicate that the source area gradually underwent more intense chemical weathering, possibly due to climatic and/or tectonic variations. On the other hand, an upward decrease in the CIA indices of the Upper Cretaceous profiles generally demonstrate that the sediments were derived from a relatively less-weathered source terrain, reflecting an increased erosion rate likely due to increasing tectonic activity. The compositional immaturity of the analysed sandstone samples is typical of subduction-related environments, and their SiO2/Al2O3 and K2O/Na2O ratios and Co, Sc, Th and Zr contents reflect their oceanic and continental-arc settings.
Keywords: shale and sandstone; geochemistry; provenance; hydraulic sorting; alteration; Yusufeli-Artvin; northeastern Turkey